Frequency of and Factors Associated With Severe Maternal Morbidity. Issue 1 (March 2015) - Grobman, W.A.; Bailit, J.L.; Rice, M.M.; Wapner, R.J.; Reddy, U.M.; Varner, M.W.; Thorp, J.M.; Leveno, K.J.; Caritis, S.N.; Iams, J.D.; Tita, A.T.; Saade, G.; et al.
Abstract : ( Obstet Gynecol . 2014;123(4):804–810)